Latest Technological Advances with MCP-PMTs. Issue 1 (1st November 2022) - Lehmann, A; Belias, A; Dzhygadlo, R; Gerhardt, A; Lehmann, D; Peters, K; Schepers, G; Schwarz, C; Schwiening, J; Traxler, M; Schmitt, L; Böhm, M; et al.
Abstract : This paper discusses the most recent advances with 2-inch MCP-PMTs. The status in terms of lifetime, detection efficiency, rate capability, time resolution, and gain behavior in magnetic fields are summarized. Significant progress in collection (CE) and quantum efficiency (QE) led to an excellent detection efficiency DQE = QE*CE of ∼30%. With a new DAQ setup up to several hundred anode pixels can be read out simultaneously in 3D allowing a glance "inside the PMT". Parameters like dark count rates and ion afterpulsing are measurable as a function of the incident photon position as well as the temporal and spacial spread of recoil electrons and electronic and charge-sharing crosstalk even inside a magnetic field.